The context of the supervision group: environment for training therapists and supervisors (Brazilian Journal of Behavioral and Cognitive Therapy, 2012)
The literature describes many skills necessary for a Behavioral Therapist Professional, however little is discussed on the supervisor’s training process. This article presents a study carried in a Cognitive and Behavioral Therapy course on the training of a apprentice-supervisor. She followed many cases supervision’s, read the reports and participated in discussions. Then, did a search on the Behavior Analysis’s literature to find what were the abilities needed for the therapist education and training, and compared with her experience, the differences and similarities in skills and the contingencies of the behavior of each supervision group member (senior-supervisor, apprentice-supervisor and student). It was observed that the environment of group supervision may be helpful to the process of training therapists and apprentices-supervisors. However, this issue still requires more systematized researches.
Keywords: behavior therapy; psychotherapy supervision; training; therapeutic skills